Social Impact of Blust Fishing and Cyanide Fishing Practice to Fishermen - Wahid, Abdul (Universitas Muhammadiyah Surakarta, 2015)
This study aimed to reveal damage endured by coral reefs as the result of practice of bombingand cyanide fishing in Barrang Lompo Island Makassar. One of fishing activities which have brought severe damages including in ecological and social is Bluster fishing. The social effect of this practice among others is the decline number of fishermen due to the reef conditions is getting worse. The risk of the use of cyanide is also considered as high mainly due to the safety of the diver. However, the practices have lasted for decades and the government’s efforts to prevent then have not succeeded yet. This study used a qualitative approach. The results showed the widespread practice of bombing and cyanide. The field analysis indicated the involvement of law enforcement officers in protecting the perpetrators bomber and tranquilizer which in fact damage the reefs. The role of government and law enforcement agencies in controlling bombardment of immature fish turned out to be very significant to suppress the fish bombing activities (Bluster fishing).